«Il fiotto come di fosforo» Polifonia enunciativa in Un posto di vacanza di Vittorio Sereni - Piasentini, Andrea (L’ospite ingrato, 2022)
This article analyses the form of lyrical subjectivity in Vittorio Sereni’s last poetic phase through the study of the enunciation of A Holiday Place, a poem at the textual and semantic centre of the last collection Variable Star (1981). The essay integrates the traditional methodological models of metrics and syntax with the linguistics of text and enunciation, focusing on deissi and, first of all, on the enunciative structure of the composition. It is in fact characterised by a complex articulation of the subjective voice, stratified on multiple temporal levels. From this particular situation, internally polyphonic, spring some enunciative modalities that represent the subject’s attempt to put into verse the globality of his own psychic life.